the Kinerja Reproduksi Ikan Selar Scomber crumenophthalmus di Perairan Buton Selatan Indonesia: Kinerja Reproduksi Ikan Selar Scomber crumenophthalmus di Perairan Buton Selatan Indonesia - La Ode Muhammad Rujiman Rujiman; Aslan Irunsah; La Suriadi; Ida Lapadi; Anjeli S. Paisey; Tutik Handayani; Nurbety Tarigan; Lutfi Lutfi (Jurnal Sumberdaya Akuatik Indopasifik, 2025)
Small pelagic fish resources require sustainable management to maintain their ecological and economic roles in marine ecosystems. One important approach to support sustainable fisheries is understanding the reproductive cycle of fish species. This study aimed to analyze the reproductive performance of bigeye scad (Scomber crumenophthalmus) caught by local fishers in the waters of South Buton, Indonesia.  The observed indicators included total length and body weight growth, gonad maturity stage, sex ratio, and spawning season. A total of 370 individuals of S. crumenophthalmus were sampled, with body weights ranging from 58.67 g to 105.46 g per individual. Samples were collected over nine weeks from July to September 2023. The study employed visual morphological analysis of gametes based on the stages of gonadal development (gametogenesis) through gonad maturity stages, supported by descriptive statistical analysis. The results indicated that the growth pattern of S. crumenophthalmus was isometric, meaning that body weight increased proportionally with body length. Gonad development of both males and females occurred from July to August 2023, while gonad maturation, ovulation, and spawning occurred in September 2023. Gonad development stages were identified through morphological differences including oogenesis, previtellogenesis, vitellogenesis, maturity, ovulation, and spawning phases. The captured population was dominated by males, while female individuals were capable of reproducing throughout the year, supporting the sustainability of S. crumenophthalmus resources in South Buton waters.